Tra A e B. Il tempo necessario a costruire un immaginario del paesaggio - Manfredi, Fabio (Ri-Vista. Research for landscape architecture, 2022)
Walking is a purely practical act, an ecological mode of locomotion, it is a way to read and experience the landscape in its spatial and temporal dimensions, one of the simplest and most natural forms to measure our position in it. Walking is a way in which we attribute meanings to our surroundings and it is for this reason that the theme is a sort of common ground of study for geographers, anthropologists, artists, landscape architects. In the dichotomies walk-move, plan-error, logistics-improvisation lies our predisposition to listen to a place. In the gap between a point A and a point B of a movement, lies our ability to make an experience and transform the movement into a useful and founding act for the landscape; the time between A and B is that necessary to build an imaginary of the latter.